1996
DOI: 10.1159/000227552
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Carcinoids

Abstract: This study investigated 22 patients with histologically proven primary bronchial carcinoids and in particular the relationship between assessment parameters and survival. In each patient, age, sex, smoking habits, mode of presentation, results of diagnostic investigations, methods of treatment and pathological examination of resected specimens were recorded. Follow-up was possible in all patients for at least 5 years. Patients with atypical carcinoids were 10 years older than patients with typical ones. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A variety of preoperative procedures, including octreoscan, abdominal and chest CT scan, MRI, bronchoscopy, hepatic venous sampling, and laparoscopy are all appropriate studies and particularly useful in anticipation of an intraoperative exploration. In some centers, position emission tomographic (PET) scan using the serotonin precursor 5-hydroxytryptophan (5-HT) labeled with 11 C has proved to be of considerable value [28]. On conventional ultrasonography, typical findings include a hyperechoic mass containing multiple cystic lesions, whereas low-density, moderately enhanced areas that confirm a cystic pattern are evident on CT scan.…”
Section: Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of preoperative procedures, including octreoscan, abdominal and chest CT scan, MRI, bronchoscopy, hepatic venous sampling, and laparoscopy are all appropriate studies and particularly useful in anticipation of an intraoperative exploration. In some centers, position emission tomographic (PET) scan using the serotonin precursor 5-hydroxytryptophan (5-HT) labeled with 11 C has proved to be of considerable value [28]. On conventional ultrasonography, typical findings include a hyperechoic mass containing multiple cystic lesions, whereas low-density, moderately enhanced areas that confirm a cystic pattern are evident on CT scan.…”
Section: Pancreasmentioning
confidence: 99%
“…Over 60% of carcinoids arise along the gastrointestinal tract-in particular, the small intestine, appendix, and colon [10]-a reflection of the dense neuroendocrine cell population of the gut and the conglomeration of ''regulatory cells'' necessary to sample and regulate the gut environmental milieu. Similarly, the bronchopulmonary system possesses a respiratory epithelium densely populated with Kulchitsky cells and accounts for approximately 25 percent of carcinoid tumors, comprising roughly 2% of all primary lung tumors [11].…”
mentioning
confidence: 99%
“…Several therapeutic modalities used in conjunction may be essential to achieve the best management of the disease, rather than a single invasive approach 23. In a recent review, even though 50% of patients underwent a lung resection after a single bronchoscopic resection, the authors reported that the inability to remove the remaining tumor was entirely due to the inaccessibility of the tumor 2426. Some experts believe that tumor reduction by this method may result in a more conservative surgical resection 15.…”
Section: Discussionmentioning
confidence: 99%
“…Limited bronchial disease may be treated with conservative resection and bronchoplasty. The response to systemic chemotherapy and radiotherapy is poor [7,8]. The 5-yr survival rate is 40-60% when complete resection is possible [9].…”
Section: Discussionmentioning
confidence: 99%